Decentration following small incision lenticule extraction (SMILE) in eyes with high myopia and its influence factors - Hui-Ni Lin; Hongqiang Zeng; Ruifeng Ji; Jinyu Li; Riping Zhang; Lixia Sun (Indian Journal of Ophthalmology)
Purpose: The purpose is to measure the decentration after small incision lenticule extraction (SMILE) in eyes with high myopia and analyze its influence factors. Methods: This retrospective study included 86 right eyes of 86 high myopia patients who underwent SMILE surgery in our hospital from August 2017 to December 2019. Patients were examined before the surgery and 3 months postoperatively. Objective and subjective refraction tests, intraocular pressure, aberrations, fundus examination, and corneal topography were recorded during all the follow-up visits. Indices of corneal anterior surface morphology, including the index of surface variance (ISV), index of vertical asymmetry (IVA), keratoconus index (KI), central keratoconus index (CKI), index of height asymmetry (IHA), and index of height decentration (IHD), as well as corneal tangential curvature and kappa angle, were all collected from Pentacam (Oculus GmbH, Wetzlar, Germany). Image J software was used to measure the decentration and the area of effective optic zone (EOZ). Spearman’s correlation test and multiple linear regression analysis were performed to assess relationships between variables. Results: Overall, data from 86 eyes were gathered and analyzed. The mean age of the participants was 25.43 years (SD, 6.08; range, 18 to 45 years), and 50 eyes (58.14%) were female. The baseline refractive characteristics of the patients were summarized in Table 1. At the 3-month after SMILE, the mean UCVA (LogMAR) was −0.02 ± 0.06, and the CDVA (LogMAR) was −0.04 ± 0.05. The safety index was 1.04 ± 0.14, and the efficacy index was 0.99 ± 0.15. At the 3 months after SMILE, the horizontal decentration (HD) showed significant correlations with those preoperative indexes, including spherical aberration (SA) (r = −0.28, P < 0.05), CKI (r = 0.26, P < 0.05), and Xk (X-axis of the kappa angle) (r = 0.27, P < 0.05). The vertical decentration (VD) was significantly influenced by preoperative higher-order aberrations (HOAs) (r = 0.24, P < 0.05) and Trefoil (r = 0.39, P < 0.05) and was also positively correlated with preoperative IVA (r = 0.29, P < 0.05), IHD (r = 0.33, P < 0.05), and Yk (Y-axis of the kappa angle) (r = 0.29, P < 0.05). And the total decentration (TD) was correlated with preoperative Trefoil (r = 0.30, P < 0.05), IHD (r = 0.22, P < 0.05), and Yk (r = 0.30, P < 0.05). Multiple linear regression revealed a relationship between TD and Yk (adjust R2 = 0.18, P < 0.001). Conclusions: Patients with high myopia after SMILE had achieved effective results. A larger kappa angle especially the Yk would tend to larger decentration. High IHD and the Trefoil preoperatively also influenced the decentration after surgery.